A review on pyrolysis of protein-rich biomass: Nitrogen transformation. (November 2020) - Leng, Lijian; Yang, Lihong; Chen, Jiefeng; Leng, Songqi; Li, Hailong; Li, Hui; Yuan, Xingzhong; Zhou, Wenguang; Huang, Huajun
Graphical abstract: Highlights: Content of Nitrogen in bio-oil from pyrolysis of N-rich biomass can be up to 10 wt%. Nitrogenous compounds include amines/amides, N-heterocycles, and nitriles. High bio-oil yield is generally accompanied by the high N content. Mediating biomass composition by coprocessing/pretreatment is meaningful. Engineering collection/separation procedures are necessary to control N in bio-oil. Abstract: Pyrolysis of protein-rich biomass, such as microalgae, macroalgae, sewage sludge, energy crops, and some lignocellulosic biomass, produces bio-oil with high nitrogen (N) content, sometimes as high as 10 wt% or even higher. Major nitrogenous compounds in bio-oil include amines/amides, N-containing heterocycles, and nitriles. Such bio-oil cannot be used as fuel directly since the high N content will induce massive emission of nitrogen oxides during combustion. The present review comprehensively summarized the effects of biomass compositions (i.e., elemental, biochemical, and mineral compositions) and pyrolysis parameters (i.e., temperature, heating rate, atmosphere, bio-oil collection/fractionation methods, and catalysts) on the contents of N and the N-containing chemical components in bio-oil. The migration and transformation mechanisms of N during the pyrolysis of biomass were then discussed in detail. Finally, the research gaps were identified, followed by the proposals for future investigations to achieve the denitrogenation of bio-oil.